THE IMPLEMENTATION OF MULTICULTURAL EDUCATION ON THE 2013 CURRICULUM AT YPPSB ELEMENTARY SCHOOL EAST KUTAI - Rahmawati, Indriana; Basith, Abdul (Universitas Islam Negeri Antasari Banajarmasin, 2020)
This study aims to describe the implementation of multicultural education in the 2013 curriculum at SD YPPSB East Kutai. This type of research is qualitative descriptive, by describing the results of learning observations, interviews with relevant sources, and reviewing syllabus documents, Learning Implementation Plans (RPP), teaching materials, and learning media. The findings of the implementation of multicultural education are carried out in a way; integrating into the theme of learning, making annual activities for self-development in a programmed and scheduled manner, implementing a model of school community model, character building, inculcation and practice of character values in daily life. As well as habituation by taking action on daily activities that are integrated with the annual school routine program.